2012
DOI: 10.1371/journal.pone.0036690
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Automated High-Throughput System for Zebrafish In Vivo Screenings

Abstract: The zebrafish is a vertebrate model compatible with the paradigms of drug discovery. The small size and transparency of zebrafish embryos make them amenable for the automation necessary in high-throughput screenings. We have developed an automated high-throughput platform for in vivo chemical screenings on zebrafish embryos that includes automated methods for embryo dispensation, compound delivery, incubation, imaging and analysis of the results. At present, two different assays to detect cardiotoxic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 57 publications
0
69
0
1
Order By: Relevance
“…Adrenaline, digilanid and atropine were provided by Peking University Hospital. The embryos of 24 hpf derived from the incross of kctd10 þ / À zebrafish were treated with adrenaline (250 mM), atropine (100 mM) and digilanid (10 mM), respectively [53][54][55] . After incubating at 28°C for 24 h, the larvae were anesthetized with MS-222 (ethyl-3-aminobenzoate methanesulfonate salt, Sigma-Aldrich Inc.) at 28°C.…”
Section: Tbx5mentioning
confidence: 99%
“…Adrenaline, digilanid and atropine were provided by Peking University Hospital. The embryos of 24 hpf derived from the incross of kctd10 þ / À zebrafish were treated with adrenaline (250 mM), atropine (100 mM) and digilanid (10 mM), respectively [53][54][55] . After incubating at 28°C for 24 h, the larvae were anesthetized with MS-222 (ethyl-3-aminobenzoate methanesulfonate salt, Sigma-Aldrich Inc.) at 28°C.…”
Section: Tbx5mentioning
confidence: 99%
“…At the same time, it allows for a substantial degree of automation, e.g. automated drug application by pipetting robots or automated distribution of embryos by embryo sorting devices 24,25 . The simple readout does not require automated screening microscopes or sophisticated image analysis software, yet provides a rich set of data on temporal and quantitative aspects of the studied signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The use of zebrafish (Danio rerio) has emerged as a powerful model system to monitor angiogenesis in vivo [15][16][17]. Zebrafish have been used as a model organism for research purposes for more than 20 years and therefore handling methods, optimum breeding techniques, husbandry, and maintenance are well established [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that most of the genes found in humans have at least one zebrafish orthologue [19]. The above ensures zebrafish as being highly useful for the study of complex biological processes such as cell 6 senescence and apoptosis, aging, cardiovascular system development, and drug toxicity response [15][16][17][18][19][20][21]. There are a few special characteristics of zebrafish that are worth highlighting.…”
Section: Introductionmentioning
confidence: 99%